2020
DOI: 10.33151/ajp.17.811
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Pupils: Covid-19 and the Impact on Student Paramedics

Abstract: COVID-19 is having a profound effect on student paramedics. This commentary aims to explore and discuss how student paramedics have been affected by COVID -19 and seeks to identify the perceived impact of this experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
(5 reference statements)
0
12
0
1
Order By: Relevance
“…Unlike Australia, Norway’s Ministry for Education and Research made a formal decision to integrate healthcare students, including paramedics, in the broader national healthcare response [ 17 – 19 ]. We found that a total of 61 paramedic students (56%) at OsloMet participated in the national response during the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike Australia, Norway’s Ministry for Education and Research made a formal decision to integrate healthcare students, including paramedics, in the broader national healthcare response [ 17 – 19 ]. We found that a total of 61 paramedic students (56%) at OsloMet participated in the national response during the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Following the shortage of healthcare workers in countries and regions that were hit hard early in the pandemic, such as northern Italy, discussions have taken place in several countries as to whether healthcare students, such as paramedics and nursing students, should take part in clinical work during times of crisis [ 14 , 15 ]. A large study from Canada demonstrated that 77.7% of university nursing students were willing to volunteer and work during a pandemic [ 16 ], and in Australia paramedic students expressed a willingness to participate in front-line clinical work during the COVID-19 pandemic [ 17 ]. Still, there is a scarcity of literature evaluating both willingness and involvement among paramedic students’ in public health emergencies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11). Öğrencilerin müfredatlarında COVID-19 gibi salgın hastalıklara yaklaşımlarına yer verilmesi öğrencilerin mesleğe başladığında salgına yönelik kaygı düzeylerini azaltması beklenmektedir (12). COVID -19 özellikle kronik hastaları daha fazla etkilediği ve mortalite ile sonuçlanabildiği için kronik hastalığı bulunan sağlık çalışanlarını daha fazla etkilenmektedir.…”
Section: İstatistiksel Analizunclassified
“…These challenges, while unsettling for established staff members, differ from those experienced by those undertaking their clinical placements at the time of COVID-19. Although medical students [ 5 , 6 ] and paramedic students [ 7 ] have described the unique challenges faced by their disciplines, the perspectives of psychology trainees in a front line health setting have not yet been reported.…”
mentioning
confidence: 99%